Beyond Blueprints: Exploring the influence of social science factors on engineers’ flood infrastructure design decisions - Elham Ajorlou; Mohammad Pourmatin; Ali Farhadzadeh; Majid Ghayoomi; Elizabeth Hewitt (PLoS ONE, 2026)
Communities rely on infrastructure for daily activities, and when assets are damaged during a disaster, they face significant costs, both in physical damages as well as quality of life disruptions. Most engineering research focuses on material properties and modeling to understand the outcomes of nature-infrastructure interactions; however, little research explores the human factors driving engineers’ design decisions. The objective of this exploratory qualitative work is to examine the role of human decision-making among engineers to better understand influential factors for flood infrastructure design. Open-ended interviews were conducted in 2022 with flood infrastructure engineers in the US who work on levees, dams, and breakwaters to better understand design parameter interactions with personal attitudes about risk and climate. Findings indicate four crucial areas that influence the design process: 1) Stakeholder involvement and influence; 2) Risk perception and tolerance of the engineer (and, specifically, tensions with the norms for risk in the home organization and the profession at large); 3) Personal characteristics of the engineer (such as their attitudes toward disasters based on personal experience), and 4) Key areas of weakness within the profession as a whole. This work provides a foundation to advance initial qualitative findings, and takeaways from this research can forge stronger interdisciplinary collaborations, while the regional focus on the U.S. may necessitate caution in global generalization.